2018
DOI: 10.1093/cvr/cvy209
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TLR9-NF-κB-mediated sterile inflammation improves pressure overload-induced right ventricular dysfunction in rats

Abstract: Inhibition of TLR9-NF-κB pathway‒mediated sterile inflammation improved PAB‒induced RV dysfunction in rats. This pathway plays a major role in the progression of pressure overload‒induced RV dysfunction, and is potentially a novel therapeutic target for the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Based on this information, the next analysis centered on the potential involvement of TLR-9 activation in the M. leprae-induced immune activation in these cells. For this purpose, we employed E6446, a very selective antagonist for TLR-9 used in several previous reports (21,(78)(79)(80)(81)(82). The inclusion of TLR-4 and TLR-9 ligands as negative and positive controls, respectively, in our assays reinforced the specificity of E6446 towards TLR-9.…”
Section: Discussionmentioning
confidence: 84%
“…Based on this information, the next analysis centered on the potential involvement of TLR-9 activation in the M. leprae-induced immune activation in these cells. For this purpose, we employed E6446, a very selective antagonist for TLR-9 used in several previous reports (21,(78)(79)(80)(81)(82). The inclusion of TLR-4 and TLR-9 ligands as negative and positive controls, respectively, in our assays reinforced the specificity of E6446 towards TLR-9.…”
Section: Discussionmentioning
confidence: 84%
“…In early PH, an increase in afterload induces adaptive cardiac hypertrophy to maintain RV stroke volume. However, with persistently elevated RV pressure overload, the RV dilates, which results in impaired contractility and systolic and diastolic parameters (17). We have demonstrated that administration of the anti-inflammatory P2X7R antagonist PKT100 allows sustained RV contractile performance compared with vehicle-treated bleomycin mice.…”
Section: H189 P2x7r Inhibition Improves Survival In Pulmonary Hypertensionmentioning
confidence: 89%
“…There are few reports indicating that inhibition of NF-κB is effective in pulmonary fibrosis. However, there is no report showing a direct link between genetic blockade of NF-κB in the lungs and pulmonary fibrosis [ 34 36 ]. This report provides for the first time that the genetic inhibition of NF-κB in the lungs prevents the BLM-induced lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%